SPE Annual Technical Conference and Exhibition 1986
DOI: 10.2118/15476-ms
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Pressure Tests Through the Use of Instantaneous Source Response Concepts

Abstract: introduced the log-log type curves to find out when AB:TllAcT wellbore stor~ge effects are negligible f~r a test. Later McKinley iind Earlougher and Kersch presented A general method of analysis for pressure transient type curves for the interpretation of bo?.h pressu~= tests 1s presented. This i.echnique is based on the drawdown and build up tests under the influence of pressure response of an instantaneous source and it wellbore storage and skin damage. rovides a mean to compute the first and second derivati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…The impulse derivative is calculated from ∆t 2 .d(dp w / ∆t). The concept was published originally by CincoLey et al 40 Pseudo-real gas potentials, m(p) or ψ, and pseudo times (∆t a ) would be used in the case of gas reservoirs. Given that in the impulse derivative there is a ∆t 2 rather than a ∆t, the impulse derivative log-log diagnostic cross-plot yields a slope of 2.0 during the wellbore storage period.…”
Section: Well Testingmentioning
confidence: 99%
“…The impulse derivative is calculated from ∆t 2 .d(dp w / ∆t). The concept was published originally by CincoLey et al 40 Pseudo-real gas potentials, m(p) or ψ, and pseudo times (∆t a ) would be used in the case of gas reservoirs. Given that in the impulse derivative there is a ∆t 2 rather than a ∆t, the impulse derivative log-log diagnostic cross-plot yields a slope of 2.0 during the wellbore storage period.…”
Section: Well Testingmentioning
confidence: 99%
“…Fenske 11 showed that the pressure behavior for a well that was flowed for a short period of time would match the slug test type curves. In addition, numerous authors [12][13][14][15] have shown that the fluid withdrawal can be considered to be an instantaneous source if the well is produced for a short period of time as compared to the shut-in time, This assumption has led to the development of impulse and slug testing for determination of permeability.…”
Section: Spe 90865mentioning
confidence: 99%
“…Evaluation of this flow regime, allows for the determination of reservoir transmissibility, flow capacity, and reservoir permeability. The Impulse-Fracture Iinjection Test is similar to more conventional well test methods, such as the slug test, closed chamber DST, and impulse test [26][27][28][29][30][31][32][33][34][35] . In these tests, a small volume of fluid is injected or produced from the reservoir to create a pressure perturbation that is evaluated to determine the reservoir flow properties.…”
Section: Spe 90865mentioning
confidence: 99%
“…Evaluation of this flow regime, allows for the determination of reservoir transmissibility, flow capacity, and reservoir permeability. The Impulse-Fracture Iinjection Test is similar to more conventional well test methods, such as the slug test, closed chamber DST, and impulse test [26][27][28][29][30][31][32][33][34][35] . In these tests, a small volume of fluid is injected or produced from the reservoir to create a pressure perturbation that is evaluated to determine the reservoir flow properties.…”
Section: Spe 90865mentioning
confidence: 99%